Herbal Products and Conventional Drugs – an Uneasy Alliance (Bangladesh Journal of Medical Science, 2018)
This review examines the interaction between herbal remedies and conventional (orthodox) drugs. There has been a substantial increase in the consumption of herbal remedies in recent times for various reasons. They are often combined with one another, and are often used simultaneously with conventional drugs that are taken for a wide range of disorders, both acute and chronic. The probability of a real and substantial interaction between the therapeutic agents originating from different medical paradigms is likewise expanding. Whilst most of the herbdrug interactions are undoubtedly minor, benign, and harmless, there are reports of more serious interactions. Possible reasons for specific herb-drug interactions are examined, particularly from the pharmacokinetic and pharmacodynamic perspectivesBangladesh Journal of Medical Science Vol.18(1) 2019 p.24-29